Comparison of Outcome Associated with Open Hemorrhoidectomy versus Stapled Hemorrhoidectomy in Patients with 3rd and 4th Degree Hemorrhoids - Hafeezullah, Muhammad; Anjum, Zeeshan (Biological and Clinical Sciences Research Journal, 2025)
Hemorrhoidal disease represents one of the most prevalent anorectal disorders globally, frequently necessitating surgical management in advanced stages (Grade III and IV). Among the available surgical techniques, open hemorrhoidectomy (OH) and stapled hemorrhoidopexy (SH) are widely practised, each with distinct advantages and limitations. In resource-limited healthcare settings such as Pakistan, determining the most effective and patient-centred approach remains a clinical priority. This study aimed to compare outcomes of OH and SH with respect to operative time, intraoperative blood loss, postoperative pain, and hospital stay. Methods: A randomized controlled trial was conducted in the Department of Surgery of Nishtar Hospital, Multan, from February 2023 to February 2024. Sixty patients with Grade III and IV hemorrhoids were enrolled using non-probability consecutive sampling and randomly allocated into two groups: Group A underwent stapled hemorrhoidectomy. In contrast, Group B underwent open hemorrhoidectomy using the Milligan–Morgan technique. Consultant surgeons performed all surgeries with at least 5years’ post-fellowship experience. Key outcome measures included operative time, intraoperative blood loss, postoperative pain (assessed via Visual Analogue Scale at 24 hours), and duration of hospital stay. Data were analyzed using SPSS v23, with a p-value ≤ 0.05 considered statistically significant. Results: The mean age of participants was 44.8 ± 10.3 years, with a male predominance (63.3%). The stapled group demonstrated significantly shorter operative time (17.8 ± 3.9 min vs. 28.6 ± 4.2 min, p < 0.001), reduced intraoperative blood loss (25.4 ± 8.5 ml vs. 52.3 ± 10.7 ml, p < 0.001), lower postoperative pain scores (VAS 2.4 ± 0.8 vs. 5.7 ± 1.2, p < 0.001), and a markedly shorter hospital stay (2.6 ± 0.7 days vs. 5.3 ± 1.5 days, p < 0.001) compared with the open group. Post-stratification by age, gender, and obesity revealed no significant influence on these outcomes (p > 0.05). No major postoperative complications or mortality were reported. Conclusion: Stapled hemorrhoidectomy offers substantial advantages over open hemorrhoidectomy, including reduced operative time, minimal blood loss, lower postoperative pain, and a shorter hospital stay, leading to faster recovery and improved patient comfort. These benefits, coupled with comparable safety, make SH a preferable choice for managing advanced hemorrhoidal disease in tertiary-care hospitals in Pakistan. However, cost-effectiveness analysis is warranted to evaluate its wider applicability in low-resource settings.